1994
DOI: 10.1093/infdis/170.6.1418
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Of Perinatal Hepatitis B Virus Exposure Is Dependent On Maternal Virus Load

Abstract: To evaluate the role of maternal hepatitis B virus (HBV) DNA levels in perinatal infection, two nested case-control studies were done within a cohort of 773 hepatitis B surface antigen (HBsAg)-positive Taiwanese women and their infants. As serum HBV DNA levels increased from < 0.005 to > or = 1.4 ng/mL among the hepatitis B e antigen (HBeAg)-positive mothers, the odds ratio (OR) for having a persistently infected infant increased from 1.0 to 147.0 (P for trend < .001). Among HBeAg-negative mothers, the OR for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(145 citation statements)
references
References 13 publications
11
129
0
5
Order By: Relevance
“…8 copies/ml) in HBeAg-positive women was associated with an odds ratio of 147 for chronic infection in infants ( 101 ). Even in the era of immunoprophylaxis, viremia remains a strong predictor of MTCT.…”
Section: Active-passive Immunoprophylaxis With Hepatitis B Immunementioning
confidence: 98%
“…8 copies/ml) in HBeAg-positive women was associated with an odds ratio of 147 for chronic infection in infants ( 101 ). Even in the era of immunoprophylaxis, viremia remains a strong predictor of MTCT.…”
Section: Active-passive Immunoprophylaxis With Hepatitis B Immunementioning
confidence: 98%
“…20 It should be noted that carriers with high HBV DNA levels are more likely to be infectious, as evidenced by transmission from maternal carriers to infants. 110 Occupational transmission of HBV has also been shown to occur in rare instances. 111,112 For HBV carriers who are health care workers, the Centers for Disease Control recommends that those who are HBeAg-positive should not perform invasive procedures without prior counseling and advice from an expert review panel under what circumstances, if any, they should be allowed to perform these procedures.…”
Section: Initial Evaluationmentioning
confidence: 99%
“…Earlier studies found that prophylaxis effective rate of passive-active immunoprophylaxis is approximately 100% if maternal prelabor HBV DNA levels were <5.5 log10 copies/mL, as compared with 2/3rd of cases if maternal DNA levels were more than these levels. 37,38 One Canadian study found that the maternal HBV DNA level of >8 log10 IU/mL was associated with increased likelihood of immunoprophylaxis failure. 39 Another study from Australia found that the risk of mother to infant transmission increased with maternal HBV DNA levels >8 log10 copies/mL and no transmission was seen in babies of mothers with HBV DNA levels <8 log10 copies/mL.…”
Section: Hepatitis B Virus Deoxyribonucleic Acidmentioning
confidence: 99%